Strategi Pengembangan Pemasaran Agroindustri Ikan Asin Air Tawar di Kabupaten Tulang Bawang - Abdurrokhim, Muhammad; Ibnu, Muhammad; Gultom, Dame Trully; Yanfika, Helvi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The objective of this study is to identify marketing development strategies for freshwater salted fish business actors in Tulang Bawang Regency. The research was conducted in Menggala District, East Menggala District, and Dente Teladas District, Tulang Bawang Regency. Respondents consisted of 37 business actors engaged in the processing of freshwater salted fish in Tulang Bawang Regency. This study employed a mixed methods approach, combining a quantitative descriptive approach to analyze census data and a qualitative SWOT analysis to formulate marketing development strategies for freshwater salted fish businesses in the region. The research findings indicate that the marketing development strategy adopted by these business actors is aggressive in nature. Recommended marketing development strategies include the diversification of end products based on freshwater salted fish to enhance competitiveness, economic value, and product adaptability to diverse consumer preferences; market penetration to increase the market share of freshwater salted fish products in existing markets through increased sales volume, intensified distribution, and optimized promotion; establishment of marketing partnerships/collaborations to expand distribution networks, strengthen market positioning, and improve marketing chain efficiency; and the development of domestic markets by expanding distribution through the optimization of local potential, market segmentation mapping, and reinforcement of marketing channels.